Protein - protein interactions prediction using support vector machines [compact disc] - 350965 Hany Taher Ahmed Alashwal; Safaai Deris, supervisor (2007)
Thesis (Ph.D(Sains komputer)) - Universiti Teknologi Malaysia, 2007